Materiais híbridos formados por polímeros, cobre e paládio: Catalisadores heterogêneos na síntese de compostos orgânicos de selênio e reações de Heck - Souza, Jaqueline Ferreira de (2022)
Catalysis is one of the most promising fields of chemistry, and as a contribution to this field, this Thesis explores methods for immobilizing metallic species on supports based on synthetic and natural polymers (polysaccharides) to obtain materials hybrids applicable in heterogeneous catalysis. The first contribution describes the preparation and characterization of alginate (Alg) microspheres loaded with divalent copper ions (Cu2+), which were able to catalyze the synthesis of a series of substituted pyrazole compounds via one-pot reactions. The second part discusses the preparation and characterization of a chitosan derivative (QT) modified with p-chlorodiphenylphosphine that was used as a support for the in-situ synthesis of palladium nanoparticles (PdNPs). The hybrid formed between the QT derivative and the PdNPs was tested as a catalyst in Heck-type cross-coupling (C-C) reactions. The third and last contribution reports the preparation of poly(acrylic acid) (PAAc) microparticles coated with polyethyleneimine (PEI), which were used as support for Cu2+ ions. As demonstrated, the resulting hybrid microparticles showed potential as a catalyst for the synthesis of 3-arylselanylindoles. Overall, the hybrid materials were formed mainly through the coordination and complexation of the tested metallic species with the functional groups of the polymers used. As a result, stable materials from the physical and chemical aspects were obtained. In summary, the results discussed in this Thesis are original and efficient strategies for the heterogenization of metallic species by using polymeric solid supports, enhancing their catalytic efficiency. The general characteristics of the prepared catalysts are attractive not only from an experimental point of view but also from a practical point of view.